Travelers Here in this Vale of Tears: William Penn Preaches a Funeral Sermon - Graves, Michael (Quaker studies, 2007)
William Penn, the significant seventeenth-century political figure and writer, was also an important preacher, but his role as a public speaker has received little attention, though at least two of his speeches and twelve of his impromptu sermons have survived. This essay argues that Penn's sermonic work is noteworthy through an examination of his 1688 public response to the death of Rebecca Travers, an important first-generation Quaker leader. Penn's response to Travers' death reveals his struggle to come to grips with the vicissitudes of his own life and, by implication, Travers' life. The sermon is interpreted as an instance of epideictic discourse seen against the contexts of Penn's and Travers' lives. In the sermon Penn uses the archetypal metaphor of life's journey in order to arrive at communal definition.